Analysis of the Effectiveness of Using Digital Technologies in Teaching 1st Year Medical Students - Alisa Popovich; Olena Aliyeva (Educational Challenges)
In the modern world, the amount of knowledge has increased significantly, and therefore, there is a constant need to acquire and update it. Medicine is a rapidly developing field, and it is important for the future and working doctor to constantly improve their professional skills using modern technologies.